1992
DOI: 10.1002/app.1992.070440520
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of imidization of poly(amic acid) in miscible and immiscible polymer blends

Abstract: SYNOPSISBlends of commercial poly (amic acid), LARC-PAA polymer were prepared with thermoplastic polyimide P84. The blends were shown to be miscible over a certain composition range. Chemical imidization of LARC-PAA in the blends leads to phase separation. Thermal imidization of LARC PAA in the blends was carried out in the solid state. Miscible compositions of the blend remained miscible after imidization and showed a single glass transition for each blend. Immiscible compositions after imidization remained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The bands at 1015 and 1000 cm -1 appear to be the most satisfactory. 15 The bands at 1780 and 720 cm -1 were found to be insensitive to changes that could be detected by thermal techniques in the later stages. 16 A recent study 8 also found that bands at 1780 and 720 cm -1 are affected by anhydride absorption that appears during the thermal cycle.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The bands at 1015 and 1000 cm -1 appear to be the most satisfactory. 15 The bands at 1780 and 720 cm -1 were found to be insensitive to changes that could be detected by thermal techniques in the later stages. 16 A recent study 8 also found that bands at 1780 and 720 cm -1 are affected by anhydride absorption that appears during the thermal cycle.…”
Section: Methodsmentioning
confidence: 92%
“…16 The band near 1380 cm -1 shows very little effect from anisotropy when it is normalized to the 1500 cm -1 aromatic band. 15 The use of different methods and procedures to measure imidization has undoubtedly contributed to the general lack of agreement over the degree of imidization that is attainable. The chemical structure of polyamic acid also affects the imidization process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In especial, the introduction of new building blocks will bring great impacts on imidization process. A large number of papers have devoted to study on imidization . Recently, various in situ characterizations were employed to study thermal imidization process, which were able to reveal real‐time evolution of microstructure and property of PI and attributed to the study on dynamic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…and polyvinylidene fluoride (16). In addition, other patents and published reports have described the compatibility or miscibility of the component polymers by various techniques and thermal behavior of these blends (17)(18)(19)(20)(21)(22)(23)(24)(25). Only a few papers (26,27) have discussed some mechanical and electrical properties of the blends prepared.…”
Section: Introductionmentioning
confidence: 99%